(untitled) (Fiep Bulletin - online, 2014)
INTRODUCTION: The obesity is defined, according to OMS (1995), as: “a disease in which the excess of corporal fat is so accumulated that the health can be affected”. OBJECTIVE: To describe the evolution of the epidemic of the obesity in children and adolescents and the prescription of physical exercises with safety and efficiency. METHODS: Systematic revision of the literature, accomplished by bases of electronic data (Medline/PubMed, Lilacs, Ovid, Science Direct), in national newspapers no indexed, by specific search for authors, as well as, in consultations with books published in Brazil and in the World. RESULTS: 30 studies were included. Being 14 national articles, eight international articles, five national books, three international books, observing a tendency of the publications an increase in starting from 2000. Regional dissimilarity was observed in the publications with emphasis in the South and Southeast areas. CONCLUSIONS: Although the studies related to the children and adolelescents with excess of weight corporal are increasing quantitatively in Brazil and in the World, there is a lack of literature in the prescription of physical exercises for that specific group.